High-density lipoprotein is inversely associated with psychiatric symptoms across diagnoses in patients with general psychiatric disorders - Soloey-Nilsen, Hedda; Nygaard-Odeh, Kristin; Kristiansen, Magnhild Gangsoey; Kvig, Erling Inge; Brekke, Ole Lars; Mollnes, Tom Eirik; Berk, Michael; Reitan, Solveig Klaebo (Frontiers in Psychiatry, 2025)
BackgroundLipids are essential in cell structure and function in all parts of the body including the brain. Thus, lipids are of obvious relevance in psychiatric disorders. While the role of lipids in pathophysiological processes in cardiovascular disorders are widely known, the role of lipids in function and pathophysiology of mental processes are far less established. This study aimed to explore serum lipid levels and their association in a clinical cohort with general psychiatric symptoms.MethodsA transdiagnostic sample of 132 patients was recruited from a general open psychiatric ward to this cross-sectional naturalistic study. Psychiatric symptoms were assessed using the Symptom Checklist-90-Revised (SCL-90-R). Serum levels of triglycerides (TG), low-density lipoprotein (LDL) and high-density lipoprotein (HDL) were measured, and multiple linear regression analysis were performed to investigate associations with symptom clusters from SCL-90-R.ResultsAfter correcting for the most common confounding factors, HDL was negatively associated with intensity of phobic anxiety (p=0.021), paranoid ideation (p=0.041), anger hostility (p=0.033) and interpersonal sensitivity (p=0.003) symptom clusters. No relations were found between TG, LDL and symptom clusters.ConclusionHDL was significant inversely associated with several general psychiatric symptoms. This result indicates a role for lipids in the pathophysiology of psychiatric disorders and suggests a mechanism for the increased cardiovascular risk across psychiatric diagnoses.